An integrated agriculture - nutrition program in Burkina Faso can change gender norms on land and asset ownership. - Bold, M. van den; Pedehombga, A.; Ouédraogo, M.; Quisumbing, Agnes R.; Olney, Deanna K. (International Food Policy Research Institute, 2014)
Helen Keller International (HKI) carried out a two-year Enhanced-Homestead Food Production (E-HFP) pilot program (2010–2012) in Gourma Province in eastern Burkina Faso. The program’s goal was to improve women’s and children’s nutrition and health outcomes through production and nutrition interventions. One way in which the program sought to improve its production and nutrition out-comes was by directly increasing women’s access to and control over productive assets. To accomplish this objective, HKI trained women and gave them inputs for raising small animals and growing nutrient-rich foods, as well as health-and nutrition -related education delivered through a behavior change communication (BCC) strategy (Dillon et al. 2012). HKI partnered with the Gender, Agriculture, and Assets Project (GAAP) to measure the impact of the program’s interventions on men’s and women’s accumulation, ownership, and control over productive assets, and to assess changes in norms and perceptions regarding the ownership, use, and control over these assets.